THE EFFECTS OF INTERNAL CONTROL SYSTEM ON CORPORATE GOVERNANCE: APPLICATION IN COMPANIES WITHIN THE SCOPE OF BIST CORPORATE GOVERNANCE INDEX - İÇ KONTROL SİSTEMİNİN KURUMSAL YÖNETİM ÜZERİNDEKİ ETKİLERİ: BIST KURUMSAL YÖNETİM ENDEKSİ KAPSAMINDAKİ ŞİRKETLERDE UYGULAMA - Recep Güneş; Figen Canbay Çiğdem; Yusuf Cahit Çukacı (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Internal control system and corporate governance are fundamental concepts for the managements that want to be afloat in global economy. In the study, effects of internal control system on corporate governance are tried to be determined. For this purpose, survey study was sent to chairman of executive board / executive board members, general manager / assistant general manager, internal auditor and audit committee members of 49 companies that are within the scope of BIST (Istanbul Stock Exchange) corporate governance index and data which can be used in analysis is obtained from 38 companies. After qualitative data was obtained in the study, the data was analysed in SPSS medium.